Kemampuan Berpikir Kritis Mahasiswa Pendidikan Geografi Pada Implementasi Case Based Learning dalam Mata Kuliah Geomorfologi Dasar - Yuni Andriyani Safitri -; Pamuti; Risky Nuri Amelia; Ramdani Salam (Jurnal Spatial Wahana Komunikasi dan Informasi Geografi, 2023)
Changes in the paradigm of student center-based learning are starting to take place in Indonesian universities. This is stated and emphasized in the main university performance indicators (IKU7), namely collaborative and participatory classes. At the implementation stage, various types of learning models were developed, but explicitly CBL and PjBL were used as the main raw models. The purpose of this study was to determine the effect of the application of the Case Based Learning (CBL) model on improving students' critical thinking skills. The subjects in this study amounted to 25 people with the type of quantitative research one group pretest and posttest design. The results show that the CBL model is quite effective in improving students' critical thinking skills through calculating the percentage n-gain score of 56.24%. This finding is reinforced by the high positive response of students to the learning model through perception networking through research questionnaires.